The role of hepatitis B vaccine challenge dose in patients with underlying health conditions. Issue 2 (1st February 2021) - Sticchi, L.; Iavarone, I. G.; Durando, P.; Di Biagio, A.; Schiavetti, I.; Murgia, F.; Icardi, G.
ABSTRACT: We have evaluated the immunological response to Hepatitis B virus (HBV) booster vaccine dose in 129 adults with underlying diseases in comparison with 694 subjects at occupational risk of infection, who have previously completed the primary series and resulted with anti-HBs <10 mIU/mL. After booster dose, 60.5% of the patients with underlying diseases and 14.8% of the subjects at occupational risk resulted seronegative. By comparing two groups, rate of subjects with anamnestic response was higher in at occupational risk group respect to that at risk for medical conditions (OR: 5.99 [95%IC, 3.81–9.41], p < .001). This difference was associated to gender (males/females: OR: 0.619 [95%IC, 0.421–0.910], p = .015) and age (better response for younger people, p = .011).